Stem-group stick insects (Phasmatodea) in the early Eocene at McAbee, British Columbia, Canada, and Republic, Washington, United States of America. Issue 6 (3rd March 2015) - Archibald, S. Bruce; Bradler, Sven
Abstract: Stem-group Phasmatodea, known as the Susumanioidea, are previously established from the Jurassic through the Paleocene. Here, we extend this record to the early Eocene with five new fossils: two forewings from the Klondike Mountain Formation exposures at Republic, Washington, United States of America, and three partially complete specimens from the McAbee locality in southern British Columbia, Canada. We assign both of the Republic specimens to the new genus and species Eoprephasma hichensi new genus, new species . Two of the McAbee fossils appear to represent two further new species, which we refer to as Susumanioidea species A and B for lack of clearly preserved diagnostic species-level character states. The third might belong to one of these two species, but this is unclear. In all three, the mesothorax and metathorax are not notably extended, the forewings are not shortened, the foreleg femur is straight, and species A possesses an extended, external ovipositor with an operculum (unknown in the other specimens). These conditions are rare and never found in combination in Euphasmatodea. All other stem-group Phasmatodea younger than the Early Cretaceous of China are only known from isolated wings.